Closing the Gaps in Understanding PFAS Toxicology and Metabolism - Denise K. MacMillan; Barbara A. Wetmore; Subham Dasgupta; William S. Baldwin (Toxics)
Per- and polyfluoroalkyl substances (PFAS) are nearly ubiquitous and found in rivers, soils, atmosphere, food packaging, clothing, cosmetics, commercial products, homes, drinking water, and humans and other organisms [...]